Lecturers’ perceptions of blended learning readiness / Turisiana Ahmad Buhari and Fauziah Saadah Abdul Halim - Buhari, Turisiana Ahmad; Abdul Halim, Fauziah Saadah (Universiti Teknologi MARA, Kedah, 2014)
Over the past years, many schools and learning institutions have provided websites and portals where teachers, tutors and lecturers can post and upload course information, additional exercises, tests and quizzes and even administrative announcements, so that students can conveniently access them from any location at any time. With students so eager to learn using technologies nowadays, it is no surprise that most technology savvy teachers are ready to use these types of instructional tools to help make learning more meaningful and motivating for the students. However, with the fast-paced technological advancement, some teachers are forever learning to use and integrate these technologies in their classrooms and failed, thus making them apprehensive of using technologies in language teaching and learning. This study was conducted to investigate the lecturers’ perceptions of Blended learning readiness in UiTM using i-Learn portal as the teaching and learning platform. The study involved twenty lecturers from the Academy of Language Studies, UiTM Shah Alam. Data for the analysis were collected through the use of survey questionnaires. The findings revealed that most of the lecturers are ready to implement Blended learning despite several notable concerns.